Model Pembelajaran Inkuiri Berbasis Laboratorium Untuk Meningkatkan Kreativitas Dan Hasil Belajar Siswa - Sutriswan Sutriswan; Usep Soetisna; Mulyati Arifin (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2018)
The problem in this research is the low of creativity and student learning outcomes that are the result of the learning process. Changes in the learning process of teaching paradigm centered on the teacher becomes a student-centered teaching paradigm. One model student-centered learning and the emphasis on the student's ability to acquire knowledge or experience of learning is learning Inquiry-Based Laboratory. The method used is the method mix (mixed methods) with the design of pretest and posttest control group design. The population of this research is the seven graders students of SMPN Darma Kabupaten Kuningan and while the sample was taken from one school by using two classes as the simple random sampling. The experimental group was treatment by using the Inquiry-Based Learning Laboratory, while the control group using conventional learning. The instruments used are observation sheets, worksheets student creativity, achievement test, and the student questionnaire responses. Based on the research and analysis of data, obtained an average N-gain creativity of the students of 0,706 for the control class were high and 0,780 for class experiments were high. While the average N-gain creativity of the students of 0,498 for the control class medium category and 0,633 for the experimental class medium category. The results of hypothesis testing students' creativity by using the Wilcoxon test, obtained the experimental class zhitung = 5,202 zhitung = 4,905 grade control, it indicates that the creativity of the students using inquiry-based learning Laboratory better than use of conventional models. While the calculation result of student learning outcomes by using Paired Samples t Test, obtained t hitung = 16.029 experimental class thitung = 14.627 control class, it shows that student learning outcomes in material processing of domestic wastewater using learning Inquiry-Based Laboratory better than the use of conventional modelsKeywords: Inquiry Based Laboratory; Creativity Student; Student Results